(untitled) (Journal of Coating Science and Technology, 2014)
The paper reports the role of sodium hydroxide in the synthesis of a superhydrophobic powder from polymethylhydrosiloxane (PMHS) in the presence of ethanol and water. The effects of other basic and acidic solutions as well as the absence of water were also investigated. PMHS exhibited rapid gelation (from 8 h to 2 h) by increasing the concentration of sodium hydroxide in the presence of ethanol and water. In contrast, gelation did not occur in the absence of sodium hydroxide or water or in the presence of acidic solutions. Delayed gelation (96 h to 120 h) occurred as a result of the introduction of dipotassium hydrogen phosphate trihydrate. Superhydrophobic powder was obtained by the evaporation of solvents from the gelated sol at 150 °C. The surface properties of the superhydrophobic powder were examined by scanning electron microscopy, high resolution transmission electron microscopy, N2 sorption isotherm, and X-ray diffraction. The particle size, functional groups and thermal stability of the powder were analyzed by dynamic light scattering spectroscopy, Fourier transform infrared spectroscopy, 29Si cross polarization magic angle spinning nuclear magnetic resonance spectroscopy, and thermogravimetric analysis. The surface properties of the powder were also assessed by contact angle measurements. The results showed that increasing the concentration of sodium hydroxide added to PMHS or increasing the drying temperature of the gelated sol resulted in the more rapid formation of superhydrophobic powder.